2013
DOI: 10.1111/jphs.12012
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting patients' compliance to anti-tuberculosis treatment in Yemen

Abstract: Objectives To identify the risk factors associated with patient non‐compliance to anti‐tuberculosis treatment among Yemini tuberculosis (TB) patients. Methods A prospective nested case‐control study was conducted. Non‐compliant cases were recruited from a cohort of TB patients registered between July 2007 and June 2008 in 10 governorates. Three forms were used for data collection that covered interviewing the participants and reviewing their medical cards and TB registers. Independent variables extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 11 publications
2
16
2
Order By: Relevance
“…Other studies have found long travel times to be associated with poor treatment adherence [24, 25]. This is a potential problem for people undergoing treatment in the Balimo region.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have found long travel times to be associated with poor treatment adherence [24, 25]. This is a potential problem for people undergoing treatment in the Balimo region.…”
Section: Resultsmentioning
confidence: 99%
“…Another similar study was conducted in Yemen to determine the role of gender and literacy in the diagnosis and reported that a high percentage of TB patients are illiterate [ 23 ]. Contrary to our study, a survey was conducted to find the factors that affect the compliance of TB patients to treatment in Yemen reported; the survey reported that the majority of patients were literate [ 24 ]. Our finding is considered normal, considering that the majority of people in Yemen are illiterate.…”
Section: Discussionmentioning
confidence: 98%
“…Our study shows that the majority of TB patients were below 45 years old, demonstrating that those productive ages are under a major risk of contracting TB in Yemen. A similar prospective study was conducted in Yemen to identify the risk factor associated with non-compliance to TB treatment and found that the majority of TB patients enrolled in the study were of productive age [ 24 ]. Another study was conducted in North India to assess the HRQoL Pulmonary TB and reported that the majority of patients were in their productive age [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Non-adherence to treatment often results from inadequate knowledge or understanding of the disease and its treatment. [9][10][11][12][13][14] Literature indicates that TB control can significantly be enhanced if more concern is given to improve knowledge and attitudes towards disease. [15] To the best of our knowledge and through extensive literature review, no studies have been reported from Yemen focusing on knowledge of TB and its treatment.…”
Section: Introductionmentioning
confidence: 99%